PKM Gizi Seimbang Anak Usia Pra Sekolah di TK Islam Baiturrahim - Ariyanto Ariyanto; Tina Yuli Fatmawati; Nel Efni (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Parenting is one of the factors that greatly affect nutritional status such as giving full attention and affection to children, giving sufficient time to pay attention to nutritional intake so that children's nutritional status becomes better. TK Islamic Baiturrahim is one of the kindergartens located in kel. Selamat Kec. Telanaipura, Jambi City. The purpose of this service is to increase the knowledge of parents in fulfilling children's balanced nutrition including: definition, goals, principles, contents of my plate, factors that influence toddler food intake and menu settings. This community service activity was carried out at the Baiturrahim Islamic Kindergarten, Jambi City, in the classroom. This service is carried out from March to July 2022 for the parents of 20 students. The purpose of service to increase the knowledge of parents of students in fulfilling children's balanced nutrition includes: definition, goals, principles, contents of my plate, factors that affect toddler's food intake and menu settings. The service method applied is lecture, discussion, mentoring, physical examination including measurement of height and weight, determining BMI. The results showed that there was an increase in mother's knowledge about the regulation of balanced nutrition in her child. After education, 100% of the mothers present were able to understand about balanced nutrition in children. Mothers can also apply and serve a balanced menu every day